Evaluation of sinonasal-related quality of life of 49 patients undergoing endoscopic skull base surgery - Yijie Zhong; Zeyi Deng; Hailing Chen; Qianhui Qiu (Brazilian Journal of Otorhinolaryngology, 2024)
Objective: This study aimed to evaluate the sinonasal-related Quality of Life (QoL) in patients undergoing endoscopic skull base surgery. Methods: A retrospective study was performed, including patients with benign and malignant tumors at a single institution. Each patient completed the 22-Item Sino-Nasal Outcome Test (SNOT-22) and the Empty Nose Syndrome 6 Item Questionnaires (ENS6Q) to assess their perceived QoL at least 2-months after treatment. Results: Forty-nine patients were enrolled in this study. The average score was 25.1 (Stander Deviation [SD] 14.99) for SNOT-22 and 6.51 (SD = 5.58) for ENS6Q. Analysis of the overall results for the SNOT-22 showed that olfactory damage was the most serious syndrome. The most frequently reported high-severity sub-domains in SNOT-22 were nasal symptoms and sleep symptoms. Nasal crusting was the most severe item in ENS6Q according to the report. Nine patients (18.4%) had a score higher than 10.5 which indicates the high risk of Empty Nose Syndrome (ENS). SNOT-22 score was related to the history of radiotherapy (p <  0.05), while the ENS6Q score was not. Conclusions: The possibility of patients suffering from ENS after nasal endoscopic skull base surgery is at a low level, although the nasal cavity structure is damaged to varying degrees. Meanwhile, patients undergoing endoscopic skull base surgery were likely to suffer nasal problems and sleep disorders. Patients who had received radiotherapy have a worse QoL than those without a history of radiotherapy. Level of evidence: Level 3.